UBX‐390: A Novel Androgen Receptor Degrader for Therapeutic Intervention in Prostate Cancer - Soohyun Lee; Hwa‐Ryeon Kim; Yaejin Woo; Jiyoung Kim; Han Wool Kim; Ji Youn Park; Beomseon Suh; Yuri Choi; Jungmin Ahn; Je Ho Ryu; Jae‐Seok Roe; Jaewhan Song; et al. (Advanced Science, 2024)
Abstract The androgen receptor (AR) is an attractive target for treating prostate cancer, considering its role in the development and progression of localized and metastatic prostate cancer. The high global mortality burden of prostate cancer, despite medical treatments such as androgen deprivation or AR antagonist therapy, highlights the need to explore alternative strategies. One strategy involves the use of heterobifunctional degraders, also known as proteolysis‐targeting chimeras, which are novel small‐molecule therapeutics that inhibit amplified or mutated targets. Here, the study reports a novel cereblon‐based AR degrader, UBX‐390, and demonstrates its superior activity over established AR degraders, such as ARV‐110 or ARCC‐4, in prostate cancer cells under short‐ and long‐term treatment conditions. UBX‐390 suppresses chromatin binding and gene expression of AR and demonstrates substantial efficacy in the degradation of AR mutants in patients with treatment‐resistant prostate cancer. UBX‐390 is presented as an optimized AR degrader with remarkable potential for treating castration‐resistant prostate cancer.